O atletismo nos cursos de graduação em educação física - Silva, Eduardo Vinícius Mota E; Darido, Suraya Cristina [UNESP] (Universidade Estadual Paulista, 2011)
This study has the purpose to investigate the characteristics and the role of the athletics-related sports disciplines in four Physical Education undergraduate courses. In order to reach the goal, it was conducted as a qualitative-type research. Data was collected through documental analysis on disciplines briefings and programs, and also from classes observations and interviews with professors and students from the institutions (two State-boarded and two private) responsible for the courses. Through these analyses it was perceived that those disciplines have surpassed some characteristics of the traditional undergraduate program, which is based on sports. Regarding the role of the disciplines, it was noted that professors consider them as responsible for providing students with basic conditions, so they could benefit from sports as instrumental subjects for their professional intervention.

Este estudo propõe-se a investigar o papel e as características do ensino das disciplinas relacionadas à modalidade esportiva Atletismo em quatro cursos de graduação em Educação Física do estado de São Paulo. Para isto, utilizou-se de uma pesquisa do tipo qualitativa. Os dados foram coletados por meio de análise documental das ementas e programas; da observação de aulas e de entrevistas realizadas com professores e alunos das instituições (duas públicas e duas privadas) responsáveis por estes cursos. Por meio destas análises verificou-se que estas disciplinas têm superado algumas características relativas ao modelo curricular tradicional - esportivo. Quanto ao papel destas disciplinas, notou-se que os docentes a consideram como as responsáveis por dar condições básicas aos alunos, para que possam usufruir a modalidade esportiva como instrumental para as intervenções no mercado de trabalho.
The athletics in physical education undergraduate courses
Keywords: Athletics; Professional Education; Undergraduate Program; Atletismo; Formação Profissional; Currículo